Survey of Physical Activity Levels in Early Childhood - Livia Mala Anjelina Anjelina; Supriatna Supriatna; Nurrul Riyad Fadhli (CV Rezki Media, 2022)
Background: Teachers and parents need to know and understand the importance of physical activity in pre-school-age children. Good physical activity will affect children's development, both in motor and cognitive aspects that can support learning achievement at school. Objectives: This study aimed to determine the level of physical activity of PAUD Al-Abada students aged 4-5 years in Kediri City with a total of 11 students using the TGMD (Test of Gross Motor Development) test. Methods: The method used in this research is descriptive quantitative, which aims to provide a real picture of what is in the field about the physical activity of Al-Abada early childhood students aged 4-5 years in the city of Kediri. Results: From the results of the tests that have been carried out, the results of the locomotor test have an average of 33.04 (Above Average), and the object control test obtained an average of 38.54 (above average). The overall data shows that children are categorized as Very poor (0%), poor (0%), bellows average (9%), average (18%), above average (37%), superior (18%), very superior (18%). Conclusion: Based on the tests that have been carried out, it can be concluded that the locomotor and object control results showed above-average values.